Synthesis and Biological Evaluation of 3‐Arylindazoles as Selective MEK4 Inhibitors. (19th February 2019) - Deibler, Kristine K.; Schiltz, Gary E.; Clutter, Matthew R.; Mishra, Rama K.; Vagadia, Purav P.; O'Connor, Matthew; George, Mariam Donny; Gordon, Ryan; Fowler, Graham; Bergan, Raymond; Scheidt, Karl A.
Abstract: Herein we report the discovery of a novel series of highly potent and selective mitogen‐activated protein kinase kinase 4 (MEK4) inhibitors. MEK4 is an upstream kinase in MAPK signaling pathways that phosphorylates p38 MAPK and JNK in response to mitogenic and cellular stress queues. MEK4 is overexpressed and induces metastasis in advanced prostate cancer lesions. However, the value of MEK4 as an oncology target has not been pharmacologically validated because selective chemical probes targeting MEK4 have not been developed. Optimization of this series via structure–activity relationships and molecular modeling led to the identification of compound 6 ff (4‐(6‐fluoro‐2 H ‐indazol‐3‐yl)benzoic acid), a highly potent and selective MEK4 inhibitor. This series of inhibitors is the first of its kind in both activity and selectivity and will be useful in further defining the role of MEK4 in prostate and other cancers. Abstract : The first of its kind : MEK4 is overexpressed and induces metastasis in advanced prostate cancer lesions. In this study we leveraged a MEK kinase platform we previously developed, for mapping the pharmacological relatedness of MEK kinase family members, to identify new potent and selective MEK4 inhibitors. We used computational docking, in vitro testing, and preliminary cellular data to guide the optimization of this novel series of compounds as the first of its kind in both activity and selectivity.